The Relationship between Self-Efficacy and Academic Procrastination in the Undergraduate Nursing Student Program at the University of Jember - Azizah, Nuha Aliyah Nur; Purwandari, Retno; Nur, Kholid Rosyidi Muhammad (Universitas Negeri Surabaya, 2024)
Abstract Background: Academic procrastination or delays in the academic field are caused by low self- efficacy wich results in a person’s inability to complete assignments. Objective: The purpose of this study was to investigate the connection between nursing students' academic procrastination and self-efficacy. Method: This study utilized observational scientific plan with a cross sectional methodology. The proportionate stratified random sampling method was used for each class to select the 229 students who participated in this study as respondents.Questionnaire General Self Efficacy Scale (GSES) was used to measure self-efficacy, while Procrastination Assessment Student Scale (PASS) to measure academic procrastination in students. With a significance level of 0.05, the spearman-rank correlation test was used to analyze the data. Results : The findings revealed a p-value of 0,073. This demonstrates that nursing students at Jember University have no significant relationship between academic procrastination and self-efficacy. Conclusion : Further research is needed on other factors that can lead to academic procrastination behavior such as peers, the environment, and differences in views on assignments Abstrak Latar Balakang :Prokrastinasi akademik atau keterlambatan dalam bidang akademik disebabkan oleh rendahnya self efficacy yang mengakibatkan ketidakmampuan seseorang dalam menyelesaikan tugas. Tujuan : Tujuan dari penelitian ini adalah untuk menyelidiki hubungan antara prokrastinasi akademik mahasiswa keperawatan dan self-efficacy. Metode: Penelitian ini menggunakan rancangan ilmiah observasional dengan metodologi cross sectional. Metode proportional stratified random sampling digunakan untuk setiap kelas untuk memilih 229 siswa yang berpartisipasi dalam penelitian ini sebagai responden. Kuesioner General Self Efficacy Scale (GSES) digunakan untuk mengukur self-efficacy, sedangkan Procrastination Assessment Student Scale (PASS) untuk mengukur penundaan akademik pada siswa. Dengan tingkat signifikansi 0,05, uji korelasi rank spearman digunakan untuk menganalisis data. Hasil : Temuan mengungkapkan p-nilai 0,073. Hal ini menunjukkan bahwa mahasiswa keperawatan di Universitas Jember tidak memiliki hubungan yang signifikan antara prokrastinasi akademik dengan efikasi diri. Simpulan : Diperlukan penelitian lebih lanjut mengenai faktor lain yang dapat menyebabkan perilaku prokrastinasi akademik seperti teman sebaya, lingkungan, dan perbedaan pandangan terhadap tugas.